Occupations related to language - Radin, Peter, artist (Ohio : Federal Art Project in Ohio, WPA, 1937)
Poster promoting occupations in the field of languages, such as interpreter, foreign buyer, correspondent, custom officer, foreign service, wireless operator, and international lawyer, showing book.